Respect, Protect, and Fulfill-or Reject, Neglect, and Regress? Children's Rights in the Time of the Russian "Gay Propaganda Law" - Caroline H. Voyles; Mariana Chilton (Harvard FXB Center for Health and Human Rights, 2019)
The "gay propaganda law"-criminalizing public messaging supporting sexual and gender minority (SGM) communities in the presence of youth-implemented within Russia in 2013 has been widely criticized by those in the international field of human rights, yet remains in effect. Although the law is supposedly protecting the well-being of children, it is likely detrimental to youth who may be sexual or gender minorities. This paper uses the 2018 conviction of a minor for violating this law to frame a discussion concerning how Russia, rather than progressively respecting, protecting, and fulfilling the rights of its people, is rejecting, regressing, and neglecting its rights obligations. In particular, we consider the rights outlined in the Convention on the Rights of the Child and the International Covenant on Civil and Political Rights to determine ways in which the Russian state could redirect its actions to support human rights for SGM people and their allies.